Marine Sponge Xestospongia sp.: A Promising Source for Tuberculosis Drug Development - Computational Insights into Mycobactin Biosynthesis Inhibition - Arfan, Arfan; Asnawi, Aiyi; Aman, La Ode (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Mycobacterium tuberculosis (MTB) remains the leading cause of infection, with a significant fatality rate, owing primarily to drug resistance. MTB contains the enzyme salicylate synthase, which regulates mycobactin production to bind iron ions from the host cell, facilitating the bacteria to grow and reproduce. This study investigates the potential of marine sponges to inhibit the MTB salicylate synthase by exploiting a computational approach combining molecular docking and dynamics simulations. Forty-six compounds from Xestospongia sp. were chosen from the Marine Natural Products database. The docking results selected four compounds (CMNPD15071, CMNPD7640, CMNPD26706, and CMNPD7639) from this sponge, which provide more negative binding energy than their inhibitors (RVE). After reclassifying their interactions, such as hydrophobic and hydrogen bonds, CMNPD15071 (Sulfuric acid mono-(8-methoxy-12b-methyl-6-oxo-2,3,6,12b-tetrahydro-1H-5-oxa-benzo[k]acephenanthrylen-11-yl) ester) and CMNPD7640 (secoadociaquinone B) performed molecular dynamics simulations to assess their stability. These two compounds show a promising stability profile compared to RVE based on RMSD, RMSF, SASA, and gyration analysis. Furthermore, the binding affinity prediction of these two compounds using the MM/GBSA calculation method reveals that CMNPD15071 (-38.48 kJ/mol) had the highest affinity for binding to MTB salicylate synthase compared to RVE (-35.36 kJ/mol) and CMNPD7640 (-26.03 kJ/mol). These findings demonstrate that compounds from Xestospongia sp. can block MTB mycobactin biosynthesis by inhibiting salicylate synthase.